2003
DOI: 10.1007/s00418-003-0548-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induces caspase activation and programmed cell death in the amitochondrial Tritrichomonas foetus

Abstract: Tritrichomonas foetus is an amitochondrial parasite protist which lacks typical eukaryote organelles such as mitochondria and peroxisomes, but possesses the hydrogenosome, a double-membrane-bound organelle that produces ATP. The cell death of amitochondrial organisms is poorly studied. In the present work, the cytotoxic effects of hydrogen peroxide on T. foetus and its participation on cell death were analyzed. We took advantage of several microscopy techniques, including videomicroscopy, light microscopy immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 84 publications
2
7
0
Order By: Relevance
“…Candida yeasts produced unfertile buds that remained closely associated with the mother cell, and appeared with or without various nuclei. The nucleus may also have an altered shape and/or with abnormal chromatin condensation that might be associated with apoptosis cell death, as previously described after treatment of C. albicans with AMB [29]; and also after treatment of Tritrichomonas foetus with hydrogen peroxide [32]. The presence of many cells with more than one nucleus may also indicate that ergosterol biosynthesis inhibitors are interfering with cytokinesis.…”
Section: Discussionmentioning
confidence: 81%
“…Candida yeasts produced unfertile buds that remained closely associated with the mother cell, and appeared with or without various nuclei. The nucleus may also have an altered shape and/or with abnormal chromatin condensation that might be associated with apoptosis cell death, as previously described after treatment of C. albicans with AMB [29]; and also after treatment of Tritrichomonas foetus with hydrogen peroxide [32]. The presence of many cells with more than one nucleus may also indicate that ergosterol biosynthesis inhibitors are interfering with cytokinesis.…”
Section: Discussionmentioning
confidence: 81%
“…RNS and ROS have been identified as inducers of apoptosis in a variety of protozoans and their effect has been reported to be concentration dependent (see reviews [10][12]). For example, H 2 O 2 at low concentrations (500 µM) caused Tritrichomonas foetus to undergo apoptosis-like death whereas at concentration of 8 mM necrotic death was observed [50].…”
Section: Discussionmentioning
confidence: 99%
“…degradation of cytoplasmatic components, hydrogenosome shape changes, plasmatic membrane projections (blebs), flagellar internalization, release of lysosomal enzyme, cell shape changes, cytoplasm vacuolization, photosensitizing (PS) externalization, and caspase activation [4,25,[28][29][30][31][32][33][34][35]. In the present study, T. foetus treated with PDT associated with photosensitizer tetrasulfonated aluminium phthalocyanine (AlPcS 4 ) showed "ladder-patterned" DNA fragments, in conventional electrophoresis assay and longer tails in Comet Assay.…”
Section: Introductionmentioning
confidence: 53%
“…It was previously reported that PDT induces cell and hydrogenosome shape changes [34] and lysosomal enzyme release [64] in T. foetus. These structural changes, together with the data reported here, indicate that PDT may have induced PCD by apoptosis, autophagy or paraptosis, which was considered an alternative form of PCD by [65].…”
Section: Discussionmentioning
confidence: 97%